A drain current model for amorphous InGaZnO thin film transistors considering temperature effects. (March 2018) - Cai, M.X.; Yao, R.H.
Highlights: Temperature dependent DC model for amorphous InGaZnO TFTs is developed. Carrier-density and temperature dependent carrier mobility is characterized. The proposed model is valid for both non-degenerate and degenerate conductions. Field effective mobility is derived by multiple trapping and release mechanism. Abstract: Temperature dependent electrical characteristics of amorphous InGaZnO (a-IGZO) thin film transistors (TFTs) are investigated considering the percolation and multiple trapping and release (MTR) conduction mechanisms. Carrier-density and temperature dependent carrier mobility in a-IGZO is derived with the Boltzmann transport equation, which is affected by potential barriers above the conduction band edge with Gaussian-like distributions. The free and trapped charge densities in the channel are calculated with Fermi-Dirac statistics, and the field effective mobility of a-IGZO TFTs is then deduced based on the MTR theory. Temperature dependent drain current model for a-IGZO TFTs is finally derived with the obtained low field mobility and free charge density, which is applicable to both non-degenerate and degenerate conductions. This physical-based model is verified by available experiment results at various temperatures.